Sustainable Amazon : Limitations and Opportunities for Rural Development - Schneider, Robert R.; Arima, Eugenio; Verissimo, Adalberto; Souza, Carlos, Jr.; Barreto, Paulo (Washington, DC: World Bank, 2013)
The report contributes to the debate surrounding land use in the Brazilian Amazon. It sets the context by reviewing the evidence concerning the deleterious effect of increasing levels of rainfall on agricultural settlement, and productivity. Next, it compares the economic future of an Amazonian community, under the traditional "predatory logging followed by ranching" model, and under sustainable logging. Last, the authors investigate the potential to create a system of national forests. The authors make four conclusions: 1) they demonstrate that increasing levels of rainfall, seriously undermine agricultural productivity, and sustainability. At the highest extreme, in the 45 percent of the Amazon with annual rainfall of over 2,200 mm, only forestry, and possibly some palm crops, are likely to be economically viable; 2) the authors assert that in this area of the Amazon, and much of the transition area (rainfall between 1,800 mm and 2,200 mm), sustainable forestry would provide more stable communities, and a higher standard of living than agriculture; 3) the authors conclude that regulatory competition, and a short local political time horizon, prevent sustainable forestry from being adapted, despite its better long-run performance; and, 4) some 10 percent of the Amazon could be put into national forests, in a way that would both meet current demand for Brazilian Amazonian timber, and reinforce the Amazon park system, which is expected to fully conserve 10 percent of the Brazilian Amazon.